Forest carbon sequestration and China's potential: the rise of a nature-based solution for climate change mitigation. Issue 2 (3rd May 2020) - Jin, Lu; Yi, Yuanyuan; Xu, Jintao
ABSTRACT: A growing interest has recently been placed on the potential of nature-based solutions to help mitigate climate change, reflecting the importance of natural ecosystems as sources and sinks for greenhouse gases. Forests are of the hot debate – that sequester and also emit carbon dioxide (CO2 ). In this paper, we estimate the forest carbon sequestration potential for China. We show that, as the government plans, by 2020, the size of China's forest carbon stock will reach 12.87 billion tons, among which 5.73 billion tons will be from afforestation and reforestation (A/R). From the up-to-date data on AR activities (by 2018), we find that only 80% of the target sinks have been met. Scenario analysis shows that the carbon sequestered by the forests in 2020 is equivalent to 13%-17% of the industrial CO2  emission that year, with 6%-8% by A/R, 4%-6% by forest-management, 3%-4% by reduced-deforestation-and-forest-degradation, and 1% by wood-product-sink.